The Structure of Leveraged Buyouts and the Free-Rider Problem - Burkart, Mike; Lee, Samuel; Petri, Henrik (Review of Financial Studies, 2026)
We study the structure of public firm buyouts in a model that features the Berle-Means problem (lack of incentives) and the Grossman-Hart problem (holdout). We find that bootstrapping, debt in excess of funding needs, and upfront fees to bidders are socially optimal and increase buyout premiums. These elements make LBO financing tantamount to a “management contract” arranged by an outside manager to receive cash and incentives to manage a firm—except the cash is funded by excess debt imposed on the firm. Our model also rationalizes why PE firms collect fees from their equity partnerships and directly from target firms.